Comparative Study of Anterior Decompression for Caries Spine using Strut Graft with and without Instrumentation (Medical Forum Monthly, 2024)
Objective: To compare the anterior decompression for caries spine using strut graft with and without instrumentation.Study Design: Comparative StudyPlace and Duration of Study: This study was conducted at the Idris Teaching Hospital of Sialkot Medical College, Sialkot from January 2018 to July 2019.Materials and Methods: A total of 60 patients were included into group A and Group B,30 patients in each. Group A patients were managed with strut graft and instrumentation using Moss Miami system. Group B patients were treated by strut graft only. The sample size is based on the past 1 year record of the hospital and about this number of patient is expected to be available. Written Informed consent was taken from every patient included in this study. The permission of ethical committee was also taken Information was then collected using Performa. Participants were selected through non probability consecutive sampling technique.Results: The outcome of and follow up of the patients immediate after operation, there was no patient of complete slippage and 50% slippage i.e. 100% patients were stable. On 3rd day, 100% patients were stable, on 1st month of discharge the patients were 100% stable, on 2nd month, there were 06(10%) patients of 50% slippage were found and there were 30/24(100/80%) patients were stable ,on 3rd month there was 6(10%) patients of 50% slippage were found and 30/24(100/80%) patients were stable. On 4th month, 2 patients(3.33%) of complete slippage and 4 patients (6.66%) of 50% slippage were found and the rest of the patient were stable ,on the fifth month the results were same as at the 4th month, at six month of discharge there were 2 patients (3.33%) of complete slippage and 04 patients(6.66%) of 50% slippage were found and the rest of the patient were stable.Conclusion: We believe that graft with instrumentation is more effective than only graft from reducing the deformity and stabilizing the vertical column in patient who have tuberculosis of the spine.